A cross-sectional study examining the pattern of acute poisoning among patients admitted to a governmental hospitals in Sana'a City, Yemen - Hassan M. Al-Mahbashi; Ahmed A. Howilah (Toxicology Reports)
Introduction: As in other countries, acute poisoning cases in Yemen are a public health problem that causes a high level of morbidity and mortality. Understanding the general aspects of this issue helps in reducing its severity. Objectives: The general goals of this study are to identify patterns of acute poisoning in Yemen, with a focus on poison type and sociodemographic variables. Methods: This is a cross-sectional study conducted on 177 cases of acute poisoning in the emergency units of three government hospitals in Sana'a, Yemen. Information was collected using a questionnaire that included all sociodemographic and medical data related to each case. Results: Cases of acute poisoning were more common in males (56.5 %) than females(43.5 %), and concentrated in the age group of 21–30 years. Approximately 66,1 % of cases occurred in individuals residing in rural areas. The percentage of non-educated individuals (53.7 %) was higher than educated ones(46.3 %). The study indicated that poisoning incidents were either intentional or non-intentional. Regarding intentional poisoning, it was categorized into homicidal or suicidal acts. The most common toxic substances involved were pesticides(30.5 %), followed by household poisoning (22.0 %), food poisoning(20.9 %), and medications(16.9 %). The most prevalent symptoms accompanying poisoning were nausea and vomiting. With regard to loss of consciousness, the percentage of those who lost consciousness was (28.8 %), and most of the cases were those who were exposed to medicines. Conclusions: Cases of acute poisoning are mostly caused by exposure to pesticides, followed by household poisoning incidents and food poisoning. Awareness about the risks of pesticides and how to handle them is crucial, especially since most poisoning cases occur in rural areas among non-educated individuals.